The speed of eating and functional dyspepsia - Jasim Al-Khazraji, Khalid A. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: dyspepsia is a common complaint, affecting about 26-41% of the general population. Investigations fail to identify organic cause in 50%–60% of functional dyspepsia. Little informations are available about whether quick eating is one of the risk factors for functional dyspepsia (FD). Objectives: To study the association between quick eating and FD. Materials and methods: The study was performed on 132 resident doctors in the medical city/Baghdad, by introducing a questionnaire derived from the Rome III criteria for diagnosis of FD and its subtypes and calculating the average daily meal duration for each one. The subjects were all Arabian, Iraqi, white resident doctors sharing the same type and amount of food. We excluded those with history of alcoholism, chronic NSAID use, documented organic gastrointestinal lesion, or with alarm features of dyspepsia , chronic systemic disease or previous history of dyspepsia. Results: The prevalence of uninvestigated dyspepsia (UD) was 37.88%, post-prandial distress syndrome (PPD): 16.67%, and epigastria pain syndrome (EPS):12.12%.Quick eating (independently on the BMI) was significantly associated with higher prevalence of FD and EPS, but not PPD. Higher BMI was associated with higher prevalence of FD and PPD (not EPS), smoking was associated with higher prevalence of FD and both subtypes, while age and gender had no effect on the prevalence of each. Conclusion: prevalence of UD increases in quick eaters regardless the BMI, Smoking and higher BMI also increase the UD prevalence.